PENGARUH INTENSITAS PERSAINGAN, DELEGASI, STRATEGI DAN PERUBAHAN SISTEM AKUNTANSI MANAJEMEN TERHADAP KINERJA ORGANISASI - Rohaelis Nuraisiah (FKIP, Universitas Banten Jaya, 2018)
This study examined the correlation between competition intensity, delegation, strategy, management accounting system changes, and organizational performance. This study took a manufacturing company located in Banten Province as the object of research. The number of samples in this study were 72 respondents. Data were analyzed by using SEM (Structural Equation Model) through the program SmartPLS (Partial Least Square) version 1.0. The results of this study states the intensity of competition has positive influence on the delegation of authority. The intensity of competition has positive influence on changes in management accounting system. The intensity of competition has positive influence on organizational performance. Delegation of authority has positive influence on changes in management accounting system. Delegation of authority has positive influence on organizational performance. Changes in accounting management system has positive effects on organizational performance. The intensity of competition has positive influence on strategy. Strategy has positive influence on organizational performance. Manufacturing companies are expected to be used as a tool for evaluation and improvement of performance. Further research is expected to add external factors variable (information technology, organizational culture, etc.) and add to more respondents. Researchers are also expected to develop further research of various other business entities, such as the banking, hotel, service, commercial or state enterprise. Scope of the research is the sampling object.